2000
DOI: 10.1007/s001250051538
|View full text |Cite
|
Sign up to set email alerts
|

Differences in HDL-cholesterol:apoA-I + apoA-II ratio and apoE phenotype with albuminuric status in Type I diabetic patients

Abstract: Diabetic nephropathy is associated with cardiovascular morbidity and mortality [1,2]. It is also associated with increased concentrations of serum total and LDL-cholesterol, triglyceride and apolipoprotein (apo)B [3,4,5,6]. In macroalbuminuria HDL-cholesterol is reduced but in microalbuminuric patients HDL-cholesterol has been reported to be reduced [3,4], unchanged [7,8] Abstract Aims/hypothesis. To examine whether the HDL-cholesterol:apoA-I + apoA-II ratio and the e2 allele are related to albuminuria at bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
2
12
1
Order By: Relevance
“…One study reported an increase in progression from normalbuminuria to microalbuminuria to macroalbuminuria in patients with the apoE2 allele; however, the decline in renal function was not examined [21]. This is in contrast to a European study which failed to find an association between E2 and either baseline albuminuria, or progression to albuminuria in type 1 diabetes [22]. There has been one previous study showing that the apoE4 allele is associated with a faster rate of decline in glomerular filtration rate in patients with diabetic nephropathy [23].…”
Section: Discussioncontrasting
confidence: 52%
“…One study reported an increase in progression from normalbuminuria to microalbuminuria to macroalbuminuria in patients with the apoE2 allele; however, the decline in renal function was not examined [21]. This is in contrast to a European study which failed to find an association between E2 and either baseline albuminuria, or progression to albuminuria in type 1 diabetes [22]. There has been one previous study showing that the apoE4 allele is associated with a faster rate of decline in glomerular filtration rate in patients with diabetic nephropathy [23].…”
Section: Discussioncontrasting
confidence: 52%
“…This finding is in agreement with the results of other studies in which triglycerides were part of multiple lipoprotein abnormalities in type 1 diabetic patients with nephropathy [19,20]. The apolipoprotein e2 allele has been reported to be a positive predictive factor for progression of renal failure in diabetes type 1 [21,22], while others could not find such association [23]. Because of the small number of patients, we analyzed progression rate by comparing e4 allele positivity vs. the rest.…”
Section: Discussionsupporting
confidence: 88%
“…[4][5][6][7] However, the influence of apoE2 in diabetic nephropathy has been denied by other authors. [53][54][55][56] At present, the controversy has not been resolved, because these studies depend on statistical evaluation in casecontrol studies only. Because many essential factors promote the development of diabetic nephropathy, such statistical methods may not be sufficient to confirm the role of apoE.…”
Section: Role Of Apoe In Diabetic Nephropathy and Other Renal Diseasesmentioning
confidence: 97%